2014
DOI: 10.1038/onc.2014.193
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cdh1 and Trp53 in the uterus induces chronic inflammation with modification of tumor microenvironment

Abstract: Type II endometrial carcinomas are estrogen independent, poorly differentiated tumors that behave in an aggressive manner. Since TP53 mutation and CDH1 inactivation occur in 80% of human endometrial type II carcinomas, we hypothesized that mouse uteri lacking both Trp53 and Cdh1 would exhibit a phenotype indicative of neoplastic transformation. Mice with conditional ablation of Cdh1 and Trp53 (Cdh1d/dTrp53d/d) clearly demonstrate architectural features characteristic of type II endometrial carcinomas, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 81 publications
(98 reference statements)
1
14
0
Order By: Relevance
“…STAT3 and IL-10 play a key role in driving immune dysregulation and severe immunodeficiency [ 25 ]. A recent study suggested that the absence of TP53 in endometrial cells initiates chronic inflammation, and a TP53 mutant in endometrial cancer cells induces normal macrophages to express genes that are involved in the inflammatory reaction through signal pathways [ 26 ]. In our study, after 24 h of S. aureus infection, the expression of TP53 in macrophages was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 and IL-10 play a key role in driving immune dysregulation and severe immunodeficiency [ 25 ]. A recent study suggested that the absence of TP53 in endometrial cells initiates chronic inflammation, and a TP53 mutant in endometrial cancer cells induces normal macrophages to express genes that are involved in the inflammatory reaction through signal pathways [ 26 ]. In our study, after 24 h of S. aureus infection, the expression of TP53 in macrophages was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Carver Biotechnology Center at the University of Illinois for library creation and sequencing as described previously . Gene set enrichment analysis (GSEA) was used to identify genetic pathways disrupted by loss of INSR activity as we performed previously . The publically available GSEA platform (http://www.broad.mit.edu) was used with the recommended settings for gene ranking and comparison with gene sets defined as significantly enriched if the FDR q value was less than 0.2 when using Pearson metrics and 1000 permutations of gene sets.…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatics analysis was performed using the database for annotation, visualization, and integrated discovery (DAVID) for a total of 199 genes (which exhibited an FDR of less than 0.1), and gene set enrichment analysis (GSEA) to identify additional genetic pathways affected by niclosamide treatment, as we previously performed [ 50 ]. Briefly, to examine genomewide expression profiles, the publicly available GSEA software package ( www.broad.mit.edu ) was used for leading edge analysis to determine whether the members of the identified gene ontology pathways were randomly distributed throughout the ranked gene list or concentrated at the top or bottom.…”
Section: Methodsmentioning
confidence: 99%